Control of microorganisms in vitro by endodontic irrigants - Estrela Cyntia R.A; Estrela Carlos; Reis Cleômenes; Bammann Lili Luschke; Pécora Jesus Djalma (Fundação Odontológica de Ribeirão Preto, 2003)
The aim of this study was to determine the minimum inhibitory concentration (MIC) and antimicrobial effectiveness by the direct exposure test of 4 endodontic irrigants [1% sodium hypochlorite (NaOCl), 2% chlorhexidine (CHX), 1% calcium hydroxide (Ca(OH)2; prepared with 1 g of Ca(OH)2 and 100 mL of sterile distilled water), a solution of Ca(OH)2 + detergent (HCT20)] for S. aureus, E. faecalis, P. aeruginosa, B. subtilis, C. albicans and a mixed culture. Microbial growth was analyzed by two methods: turbidity of the culture medium that was confirmed by Gram stain and subculture in a specific nutrient broth. In the dilution test, NaOCl solution showed MIC equal to 0.1% for S. aureus, E. faecalis, P. aeruginosa and C. albicans and equal to 1% for B. subtilis and the mixed culture. CHX (2%) presented MIC equal to 0.000002% for S. aureus, 0.02% for E. faecalis, B. subtilis, C. albicans and the mixed culture and 0.002% for P. aeruginosa. Ca(OH)2 solution (1%) showed MIC greater than 1% for all the microorganisms except P. aeruginosa for which it was equal to 1%. Calcium hydroxide solution + detergent showed MIC equal to 4.5 mL for S. aureus, P. aeruginosa, B. subtilis, C. albicans and the mixed culture and greater than 4.5 mL for E. faecalis. In the direct exposure test, NaOCl had better antimicrobial effectiveness for all microorganisms at all times. CHX (2%) was effective for S. aureus, E. faecalis and C. albicans at all times, and ineffective for P. aeruginosa, B. subtilis and the mixed culture. The other solutions showed the worst results.